(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
This paper presents an exploratory study of the relationship between wine producers and distributors in the Croatian wine sector. It focuses on the impact of distribution channels on the bargaining position of wine producers, thereby adding to the growing body of research seeking to determine the factors that influence the growth potential of the traditional agricultural sector. Due to the fragmentation on the production side of the market and a high level of concentration on the distribution side, the wine sector provides a suitable context for studying the bargaining power of agricultural (wine) producers and hypothesizing on future outcomes in terms of industry structure and growth potential. Presuming that the share of value retained by the wine producer depends on his bargaining position, two hypotheses were tested: H1: A higher degree of self-reliance improves a wine producer’s bargaining position and H2: A higher number of distribution channels improves a wine producer’s bargaining position. After a brief review of relevant scientific literature, five regression models were created and tested on a sample of 124 Croatian wine producers, which yielded statistically significant results confirming the hypotheses. The final model controls for production volume, number of labels and respective region. The paper ends with some general conclusions and recommendations for future research.